Exercise Intensity and Gender Difference of 3 Different Salsa Dancing Conditions - Emerenziani, G. P.; Guidetti, L.; Gallotta, M. C.; Franciosi, E.; Buzzachera, C. F.; Baldari, C. (International Journal of Sports Medicine, 2013)
The aims of this study were to estimate the difference in exercise intensity (METs), energy cost (EE) and gender difference between a typical salsa lesson (TSL), rueda de casino lesson (RCL), and salsa dancing at a night club (SDN). Subjects performed 1 pre-testing session and 3 testing conditions. During the pre-testing session height, weight and V˙O2max were assessed. During the testing conditions all subjects performed 3 different kinds of salsa dance. Heart rate was assessed during each dance condition. The exercise intensity of the 3 salsa dancing conditions was moderate ranging from 3.9 to 5.5 METs. A significant difference between genders for HRpeak (P=0.01), max%HRR (P=0.006) and mean EE (P=0.02) were observed. Significant gender×condition interactions for HRpeak (P=0.03), mean %HRR (P=0.02), mean METs (P=0.02) and mean EE (P=0.02) were found. In addition, a significant main effect for each condition was found in all variables (P<0.01). Our results showed that the exercise intensities of all 3 salsa dancing conditions were moderate. Findings showed some significant differences in exercise intensity between males and females and within conditions. Salsa dancing could be useful in achieving a significant training effect in people who have a low level of fitness.
Keywords: physical activity; well-being; energy cost; gender differences